Daily use of lateral flow devices by contacts of confirmed COVID-19 cases to enable exemption from isolation compared with standard self-isolation to reduce onward transmission of SARS-CoV-2 in England: a randomised, controlled, non-inferiority trial. Issue 11 (November 2022) - Love, Nicola K; Ready, Derren R; Turner, Charlie; Verlander, Neville Q; French, Clare E; Martin, Alex F; Sorensen, Tina B; Metelmann, Soeren; Denford, Sarah; Rubin, G James; Yardley, Lucy; Amlôt, Richard; et al.
Summary: Background: In the UK, during the study period (April to July, 2021), all contacts of people with COVID-19 were required to self-isolate for 10 days, which had adverse impacts on individuals and society. Avoiding the need to self-isolate for those who remain uninfected would be beneficial. We investigated whether daily use of lateral flow devices (LFDs) to test for SARS-CoV-2, with removal of self-isolation for 24 h if negative, could be a safe alternative to self-isolation as a means to minimise onward transmission of the virus. Methods: We conducted a randomised, controlled, non-inferiority trial in adult contacts identified by COVID-19 contact tracing in England. Consenting participants were randomly assigned to self-isolation (single PCR test, 10-day isolation) or daily contact testing (DCT; seven LFD tests, two PCR tests, no isolation if negative on LFD); participants from a single household were assigned to the same group. Participants were prospectively followed up, with the effect of each intervention on onward transmission established from routinely collected NHS Test and Trace contact tracing data for participants who tested PCR-positive for SARS-CoV-2 during the study period and tertiary cases arising from their contacts (ie, secondary contacts). The primary outcome of the study was the attack rate, the percentage of secondary contacts (close contacts of SARS-CoV-2-positive study participants) who became COVID-19 cases (tertiary cases) in each group. Attack rates were derived from Bernoulli regression models using Huber-White (robust) sandwich estimator clustered standard errors. Attack rates were adjusted for household exposure, vaccination status, and ability to work from home. The non-inferiority margin was 1·9%. The primary analysis was a modified intention-to-treat analysis excluding those who actively withdrew from the study as data from these participants were no longer held. This study is registered with the Research Registry (number 6809). Data collection is complete; analysis is ongoing. Findings: Between April 29 and July 28, 2021, 54 923 eligible individuals were enrolled in the study, with final group allocations (following withdrawals) of 26 123 (52·6%) participants in the DCT group and 23 500 (47·4%) in the self-isolation group. Overall, 4694 participants tested positive for SARS-CoV-2 by PCR (secondary cases), 2364 (10·1%) in the self-isolation group and 2330 (8·9%) in the DCT group. Adjusted attack rates (among secondary contacts) were 7·5% in the self-isolation group and 6·3% in the DCT group (difference of –1·2% [95% CI –2·3 to –0·2]; significantly lower than the non-inferiority margin of 1·9%). Interpretation: DCT with 24 h exemption from self-isolation for essential activities appears to be non-inferior to self-isolation. This study, which provided evidence for the UK Government's daily lateral flow testing policy for vaccinated contacts of COVID-19 cases, indicated that daily testing with LFDs could allow individuals to reduce the risk of onward transmission while minimising the adverse effects of self-isolation. Although contacts in England are no longer required to isolate, the findings will be relevant for future policy decisions around COVID-19 or other communicable infections. Funding: UK Government Department of Health and Social Care.